Development of iOS app for power system - Yeo, Wei Xuan (Nanyang Technological University, 2024)
The power system as a subject is complex due to its complicated calculation process. Its calculations, particularly the Gauss-Seidel and Newton-Raphson methods, involve many iterations to get the final solutions. This calculation is tedious, and careless mistakes can quickly occur during the process. The final year project aims to develop a mobile app that helps educate users on the Gauss- Seidel and Newton Raphson learning process and provide a final solution for the iteration method. The mobile app will be developed using Flutter as the framework and Dart as the programming language. The mobile app will consist of a step-by-step learning process display to provide users with all the necessary information and greater clarity.